Mapping The Shifting Trends in ESG Research Across Countries, Pillars, and Industries - Agnes Monica Sihotang; Arif Imam Suroso; Suhendi Suhendi (Universitas Prasetiya Mulya, 2026)
This study conducts a Systematic Literature Review (SLR) of Environmental, Social, and Governance (ESG) research published between January 2015 - June 2025. Using the PRISMA 2020 protocol, 129 Scopus-indexed articles were analyzed through thematic mapping and bibliometric visualization. The analysis shows that ESG research remains geographically concentrated in developed economies such as China, the United States, and Europe, while contributions from emerging markets are still limited. Thematic patterns indicate an evolution from an early emphasis on environmental concerns to heightened attention on social issues during the COVID-19 pandemic. It is also followed by a growing focus on governance and integrated approaches in recent years. Sectoral industries perspectives reveal that most studies adopt a cross-industry orientation with particular attention given to banking and technology. Meanwhile, industries that play central role to developing countries remain largely overlooked. These findings emphasize the importance of broadening geographical coverage and sectoral depth to enhance both theoretical contributions and policy relevance in ESG research.